Exploring inclusive Practices, Successes and Challenges experienced by teachers in Implementation of Inclusive Education in one selected mainstream school in Ekurhuleni North district, South Africa - Mamogobo, Amogelang Mankurwane (University of the Witwatersrand, Johannesburg, 2023)
The realization of inclusive education in South African schools has been controversial. Despite numerous policies enacted, numerous studies have found low levels of implementation of inclusive education in schools. The study aimed to explore inclusive practices, successes, and challenges of inclusive education implementation in the selected mainstream school. In order to explore the study, three research questions were addressed, which inclusive practices are being implemented by teachers in the selected school? What are the successes of inclusive education implementation in mainstream primary schools in Gauteng? What are the challenges affecting the implementation of inclusive education in mainstream primary schools in Gauteng? Both the inclusive pedagogical method and the social model of disability approach served as the theoretical foundation for the current investigation. The present study was conducted using a qualitative research methodology with a case study as the chosen research design within an interpretivist research paradigm. The researcher used a non-probability sampling technique more specifically the purposive sampling approach, in which the researcher used their own judgment to sample the research participants. In relation to the data collection methods. The researcher used non-participant observations and semi- structured interviews to gather data. Interviews with just six individuals and one classroom observation were conducted. The study's conclusions reaffirmed the importance of inclusivity; there were many inclusive practices that were widely used in the study; and the school had achieved a number of successes, such as the purchase of infrastructure and the successful implementation of intervention programs to improve the learning experience of students who faced barriers. The challenges in the present study were vast and categorized into three sub-sections: teacher-related, school-related, and community-related challenges. The study's findings indicate that there have been major efforts to integrate inclusive policies, some of which have been successful, but that there are still many difficulties in schools. The report suggests that the Department of Education give priority to in-service teachers' initial and ongoing training in inclusive practices for a range of learner disabilities.
A research project submitted in the fulfilment of the requirements for the degree of Master of Education, to the Faculty of Humanities, Wits School of Education, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Inclusive education; Inclusive practices; Successes; Challenges; UCTD; SDG-4: Quality education